Central Acting Hsp10 Regulates Mitochondrial Function, Fatty Acid Metabolism, and Insulin Sensitivity in the Hypothalamus - Kristina Wardelmann; Michaela Rath; José Pedro Castro; Sabine Blümel; Mareike Schell; Robert Hauffe; Fabian Schumacher; Tanina Flore; Katrin Ritter; Andreas Wernitz; Toru Hosoi; Koichiro Ozawa; et al. (MDPI AG, 2021)
Mitochondria are critical for hypothalamic function and regulators of metabolism. Hypothalamic mitochondrial dysfunction with decreased mitochondrial chaperone expression is present in type 2 diabetes (T2D). Recently, we demonstrated that a dysregulated mitochondrial stress response (MSR) with reduced chaperone expression in the hypothalamus is an early event in obesity development due to insufficient insulin signaling. Although insulin activates this response and improves metabolism, the metabolic impact of one of its members, the mitochondrial chaperone heat shock protein 10 (Hsp10), is unknown. Thus, we hypothesized that a reduction of Hsp10 in hypothalamic neurons will impair mitochondrial function and impact brain insulin action. Therefore, we investigated the role of chaperone Hsp10 by introducing a lentiviral-mediated Hsp10 knockdown (KD) in the hypothalamic cell line CLU-183 and in the arcuate nucleus (ARC) of C57BL/6N male mice. We analyzed mitochondrial function and insulin signaling utilizing qPCR, Western blot, XF96 Analyzer, immunohistochemistry, and microscopy techniques. We show that Hsp10 expression is reduced in T2D mice brains and regulated by leptin in vitro. Hsp10 KD in hypothalamic cells induced mitochondrial dysfunction with altered fatty acid metabolism and increased mitochondria-specific oxidative stress resulting in neuronal insulin resistance. Consequently, the reduction of Hsp10 in the ARC of C57BL/6N mice caused hypothalamic insulin resistance with acute liver insulin resistance.